Philosophy, Cultural Philosophy and Sociology - Watier, Patrick; Amat, Matthieu; Mora, Emanuela (Simmel Studies)

(untitled) (Georg Simmel Gesellschaft, 2018)
Every sociology rests on representations that are not explicitly thematised, and are in concordance with an atmosphere and cultural formations. These representations correspond to what Panofsky called a mental habit. which is transferable from one field of activity or thought to another. The essay shows how both the themes of individuality and of Bildung play back on G. Simmel's conception and place of the "social" and, consequently, on his sociological view.